(untitled) (Baghdad Science Journal, 2020)
Antibiotic resistance is the capability of the strains to resist or protect themselves from the effects of an antibiotic. Such a resistance towards the current antimicrobials leads to the search of novel antimicrobials. Nanotechnology has been promising in different field of science and among it is the use of nanoparticles as antibacterial agents. The gastrointestinal tract seems to be the primary reservoir of uropathogenic E.coli (UPEC) in humans. UPEC strains harbour the urinary tract and cause urinary tract infection. They cause serious ailments in terms of humans. They develop resistance and increase their virulence by forming biofilms. They also show a remarkable locomotory movement with the aid of autoinducer controlled genes (AI-2). The present study is designed to investigate the expression levels of the AI-2 controlled genes and the motility genes in the presence of nanomaterials. RT PCR amplification together with the antibacterial and motility studies were done to compare the significant effect of silver nanoparticles on the pathogen. S-adenosylmethionine assay was also done to confirm the role of the treatment on the repression of the AI-2 genes. The results showed silver nanoparticles have significant effect on the motility studies. The relative expression and repression of motB gene was under the control of AI-2 kinase protein. This confirms the possible role of the nanoparticles towards the pathogen UPEC. There was also an inhibition on the biofilm formation under the effect of the nanoparticle treatment. The study concludes that the silver nanoparticles could be used as a novel antibacterial agent against the UPEC strains and thereby inhibits the antibacterial resistance.